Incidence of Atrial Fibrillation and Mineralocorticoid Receptor Activity in Patients With Medically and Surgically Treated Primary Aldosteronism - Hundemer, Gregory L. (JAMA Cardiol, 2018)
IMPORTANCE: Primary aldosteronism (PA) is an ideal condition to evaluate the role of the mineralocorticoid receptor (MR) in the pathogenesis of atrial fibrillation (AF). OBJECTIVE: To investigate whether MR antagonist therapy or surgical adrenalectomy in PA influence the risk for incident AF. DESIGN: This cohort study included patients aged 18 years and older. Patients with PA and age-matched patients with essential hypertension were identified via electronic health records. Patients with a history of AF, myocardial infarction, congestive heart failure, or stroke were excluded. Data were collected between 1991 and the end of 2016 in an academic medical center, with a mean follow-up duration of approximately 8 years. EXPOSURES: Patients with PA treated with MR antagonists or surgical adrenalectomy were compared with patients with essential hypertension. Patients with PA who were treated with MR antagonists were categorized by whether their plasma renin activity remained suppressed (< 1 ng/mL/h) or substantially increased (≥ 1 ng/mL/h), as proxies for insufficient or sufficient MR blockade. MAIN OUTCOMES AND MEASURE: Incident AF. RESULTS: A total of 195 patients with PA who were treated with MR antagonists and 201 patients with PA treated with surgical adrenalectomy were included, as well as 40 092 age-matched patients with essential hypertension. Despite similar blood pressure at study entry and throughout follow-up, patients with PA who were treated with MR antagonists whose renin remained suppressed had a higher risk for incident AF than patients with essential hypertension (adjusted HR, 2.55 [95% CI, 1.75-3.71]). They also had an adjusted 10-year cumulative AF incidence difference of 14.1 (95% CI, 6.7-21.5) excess cases per 100 persons compared with patients with essential hypertension. In contrast, patients with PA who were treated with MR antagonists and whose renin increased and patients with PA who were treated with surgical adrenalectomy had no statistically significant difference in risk for incident AF compared with patients with essential hypertension. CONCLUSIONS AND RELEVANCE: When compared with patients with essential hypertension, patients with PA treated with MR antagonists such that renin remained suppressed (as a proxy for insufficient MR blockade) had a significantly higher risk for incident AF; however, treatment of PA with MR antagonists to substantially increase renin (suggesting sufficient MR blockade), or with surgical adrenalectomy (to remove the source of aldosteronism), was associated with no significant difference in risk for developing AF. These findings add to the growing body of evidence suggesting that MR blockade may be a potential therapy to decrease the incidence of AF.